ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWAT MENGGUNAAN ALAT PELINDUNG DIRI (HANDSCOON) DI RSUD BENDAN KOTA PEKALONGAN - Darmawati .; M. Projo Angkasa; Isrofah . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Personal protective equipment is a part of the hazard control in the workplace that should always be used  to  ensure  safety,  especially  in  the  use  of  handscoon  when  the  nurse  injected  a  patient  in the hospital.This research was aimed to determine the factors that affect nurse’s compliance to the use of personal protective  equipment  (handscoon)  when  giving  injection  in  patient  rooms  of  RSUD  Bendan Pekalongan city.This study used a croos – sectional approach with a total sampling technique of 98 respondents.The  result  showed  that the  majority  of  respondents  were 31 - 35 years  old (35 respondents), female (53 respondents),  have  been  working  for 3 - 4 years (55 respondents),  and D3 - educated (58 respondents) as many as 35,7 % ; 54,1 % ; 56,1 %, and 5,2 %respectively. The majority of  respondents (55,1  %) had  a  good  knowledget. However 56,1  % respondents  had  a  poor  attitude toward. A total of 55 respondents (56,1%) stated that the availability of personal protective equipment in  the  hospital  was  less  complete.  A  total  of 68 people (69,4  %) stated  that  the  personal  protective equipment in the hospital was less convenient to use. As many as 59respondents (60,2 %) stated that the  rules  of  personal  protective  equipment  in  the  hospital  was  less  well.  Supervision  of  personal protective  equipment  also  was  stated  less  well  by 74 respondents (75,5  %), and  the  majority  of respondents (72,4 %) complied with the use of personal protective equipment when giving an injection to a patient in the inpatient rooms at RSUD Bendan Pekalongan city.This  study  concluded  that  there  was  influence  of  the  availability  of  personal  protective  equipment, attitude  toward, and  regulation  of  personal  protective  equipment  and  attitude toward  with  nurse’s compliance  in  the  use  of  personal  protective  equipment  (handscoon)  when  giving  injection  to  a patients in the patient rooms at RSUD Bendan Pekalongan city.Keywords : Factors affecting compliace, personal protective equipment and Injection.